Maintenance management of mosque in Kota Bharu Kelantan: case study of Masjid Muhammadi, Masjid Al-Sultan Ismail Petra Kubang Kerian, Masjid Sultan Muhammad II Telipot, & Masjid Sultan Mansor Kg. Sireh / Siti Nur Far’ain Salahuddin - Salahuddin, Siti Nur Far’ain (Faculty of Architecture, Planning and Surveying, 2015)
Maintenance management on mosque is very important to make sure the buildings are functional and have good attraction to occupants. Besides, maintenance work or activities cannot separate with the involvement of cost which sometimes high depends to type of damages occur. Maintenance work of mosque is more focus to cleaning aspect, security, and others aspect. This research aim to assess maintenance management of mosque in Kota Bharu. The objectives of this research are to understand the maintenance management of mosque, to observe the effectiveness of maintenance management of mosque, and to identify better solution in maintenance management of mosque. This study focus on maintenance management of mosque in Kota Bharu. Interviews session and observation were conducted. Interviews session involved the parties from mosque management and maintenance team work. Based on data analysis, mosque in Kota Bharu did not use in-source method of contractor, only out-source method was practice. Usually, outsource contractor quote the highest maintenance cost, does not produce the best quality of maintenance work, and it take time to find out-source contractor. Cleaning routine team work is provided by Majlis Agama Islam dan Adat Istiadat Melayu Kelantan. Mosques in Kota Bharu applied planned and unplanned maintenance. Only daily maintenance is effective, others are not effective to maintenance of mosques. Maintenance management of mosques in Kota Bharu should be improved by introducing in-source method of contractor which is have their own maintenance team workers with proper budget and schedule.